2005
DOI: 10.1002/app.21569
|View full text |Cite
|
Sign up to set email alerts
|

Starch crosslinked with poly(vinyl alcohol) by boric acid

Abstract: Starch was crosslinked with poly(vinyl alcohol) (PVA) by boric acid. A suitable plasticizer and defoamer were added to obtain the brei. A film from the starch and PVA (SP film) was prepared by casting. The effects of various factors, such as the crosslinking temperature, the PVA content, and the amounts of glycerol and boric acid, on the tensile strength and breaking elongation were studied. The results showed that the SP film prepared by boric acid crosslinking had excellent mechanical properties. The filmfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
67
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 3 publications
15
67
0
4
Order By: Relevance
“…Films made using epichlorohydrin-cross-linked starch and polyethylene (1:1 ratio) had strength ranging from 12 to 15 MPa with varying amounts of epichlorohydrin (0.1-2%), compared to 24 MPa for the 5% citric acid cross-linked films (Kim & Lee, 2002). Similarly, starch-polyethylene films cross-linked with boric acid (0.5-2.5%) had tensile strength ranging from 8.9 to 10.1 MPa and the breaking elongation decreased from 60% to 8% after cross-linking (Yin, Li, Liu, & Li, 2005). However, starchpolyvinyl alcohol films cross-linked with hexamethoxymethylmelamine had tensile strength ranging from 50 to 65 MPa, and the non-cross-linked films also had high strengths, ranging from 45 to 55 MPa (Chen, Imam, Gordon, & Greene, 1997).…”
Section: Effect Of Citric Acid Concentrationmentioning
confidence: 98%
“…Films made using epichlorohydrin-cross-linked starch and polyethylene (1:1 ratio) had strength ranging from 12 to 15 MPa with varying amounts of epichlorohydrin (0.1-2%), compared to 24 MPa for the 5% citric acid cross-linked films (Kim & Lee, 2002). Similarly, starch-polyethylene films cross-linked with boric acid (0.5-2.5%) had tensile strength ranging from 8.9 to 10.1 MPa and the breaking elongation decreased from 60% to 8% after cross-linking (Yin, Li, Liu, & Li, 2005). However, starchpolyvinyl alcohol films cross-linked with hexamethoxymethylmelamine had tensile strength ranging from 50 to 65 MPa, and the non-cross-linked films also had high strengths, ranging from 45 to 55 MPa (Chen, Imam, Gordon, & Greene, 1997).…”
Section: Effect Of Citric Acid Concentrationmentioning
confidence: 98%
“…Examples of cross-linking included use of cross-linking reagents such as poly (ethylene-co-acrylic acid) (EAA) (Lawton & Fanta, 1994), glutaraldehyde (Ramaraj, 2007;Yoon, Chough, & Park, 2007), boric acid (Sreedhar, Sairam, Chattopadhyay, Syamala Rathnam, & Mohan Rao, 2005;Yin, Li, Liu, & Li, 2005), epichlorohydrin (Sreedhar, Chattopadhyay, Sri Hari Karunakar, & Sastry, 2006), Hexamethoxymethylmelamine (HMMM) (Chen et al, 1997), and radiation (Follain, Joly, Dole, & Bliard, 2005;Khan, Bhattacharia, Kader, & Bahari, 2006;Zhai, Yoshii, Kume, & Hashim, 2002;Zhai, Yoshii, & Kume, 2003). Lawton and Fanta (1994) observed that the elongation of starch-PVOH-glycerol films could be improved by adding a small amount of (EAA).…”
Section: Chemical and Physical Modification Of Starch-pvoh Blendsmentioning
confidence: 98%
“…Thus, the mechanic properties of PVA/starch composites need further improvement to meet the demands of extensive applications. Some of the effective means commonly used to improve the properties of PVA/starch composites include chemically modified PVA or starch such as cross-linking [26][27][28][29][30][31][32], grafting [19,33,34], and surface modification [35,36]. Grafting and cross-linking reactions improve the compatibility between PVA and starch molecules, resulting in the improvement of the mechanical properties, transparency and water-resistivity or swelling properties, while retaining the biodegradability [27,31,37].…”
Section: Introductionmentioning
confidence: 99%